Determination of Cutoff of IgM ELISA for Diagnosis of Scrub typhus in Hilly Northern State of Himachal Pradesh - Gupta, Anshu (PSM Microbiology, 2018)
The aim of the study was to determine geographically relevant cutoffs for IgM ELISA in Himachal Pradesh. A total of 392 individuals including 292 patients of all age groups with clinically suspected scrub typhus and 100 healthy people were enrolled after taking a proper consent at Indira Gandhi Medical College, Shimla. An indirect ELISA that detects IgM antibodies to Orientia tsutsugamushi was performed in all serum samples. The serum samples from patients were subjected to IgM immuno?uorescent antibody (IFA) (Fuller Laboratories, USA). A receiver operating characteristic (ROC) curve was drawn for ELISA to generate cutoff for the test. A total of 192 patients were found to be positive for scrub typhus. A set of 100 sera samples collected from healthy volunteers from Shimla were used to establish region speci?c cutoff for IgM ELISA. The cut off calculated from healthy volunteer was mean OD +3 standard deviation = 0.5. The ROC curve analysis of 392 participants revealed a cutoff-OD value of 0.46 with sensitivity and speci?city of 91.7% and 99.5% respectively. Hence, a cutoff-OD value of 0.46 or 0.5 can be used as the cutoff for the diagnosis of scrub typhus for Himachal Pradesh based on our ?ndings.